2018
DOI: 10.4103/aer.aer_104_18
|View full text |Cite
|
Sign up to set email alerts
|

Use of butorphanol, fentanyl, and ketamine as co-induction agents with propofol for laryngeal mask airway insertion: A comparative study

Abstract: Background:Management of airway is of great importance in the practice of anesthesia. Supraglottic airway devices, such as laryngeal mask airway (LMA), have greatly revolutionized the management of airway both in terms of ease and degree of invasiveness. Propofol, by its inherent property of decreasing airway reflexes, is used to aid in LMA insertion. In this study, we have evaluated the LMA insertion conditions and hemodynamic stability, comparing butorphanol, fentanyl, and ketamine as co-induction agents wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…On arrival in operating room large bore intravenous cannula was placed under local infiltration. General anesthesia was begun with coinduction 10,11 by injection nalbuphine 10mg plus midazolam in dose of 0.01mg/kg. Inj.…”
Section: Methodsmentioning
confidence: 99%
“…On arrival in operating room large bore intravenous cannula was placed under local infiltration. General anesthesia was begun with coinduction 10,11 by injection nalbuphine 10mg plus midazolam in dose of 0.01mg/kg. Inj.…”
Section: Methodsmentioning
confidence: 99%
“…However, unlike propofol, it acts as a sympathetic cardiorespiratory stimulant and has pain-relieving properties [6]. In the literature, several studies have shown that hemodynamic stability can be achieved with the combined use of ketamine and propofol in pediatric cases under general anesthesia with LMA [7][8][9][10]. However, most of those studies involved sedation and general anesthesia for non-specific surgical indications and were conducted on different patient cohorts consisting of both pediatric and adult groups.…”
Section: Introductionmentioning
confidence: 99%
“…12 For this sake different co-induction agents have been used with propofol, these include ketamine, fentanyl and butorphanol. 13 Ketamine has multidimensional clinical effects. It has gained its place as a co-induction agent.…”
Section: Introductionmentioning
confidence: 99%